Development and preliminary validation of the Scleroderma Support Group Leader Self-efficacy Scale. Issue 1 (February 2018) - Pal, Nicole E.; Gumuchian, Stephanie T.; Delisle, Vanessa C.; Pépin, Mia; Malcarne, Vanessa L.; Carrier, Marie-Eve; Kwakkenbos, Linda; Peláez, Sandra; El-Baalbaki, Ghassan; Thombs, Brett D.; ,
Support groups are an important resource for people living with systemic sclerosis (SSc; scleroderma). Peer support group leaders play an important role in the success and sustainability of SSc support groups, but face challenges that include a lack of formal training. An SSc support group leader training program could improve leader self-efficacy to carry out important leadership tasks, including the management of group dynamics. However, no measures exist to assess self-efficacy among SSc support group leaders. The objective of this study was to develop and provide preliminary evidence on the reliability and validity of the Scleroderma Support Group Leader Self-efficacy Scale (SSGLSS). The SSGLSS was administered to two sets of SSc support group leaders from North America, Europe, and Australia. Study 1 participants (n = 102) completed the SSGLSS only. Study 2 participants (n = 55) completed the SSGLSS and the Oldenburg Burnout Inventory (OLBI). For both studies, we evaluated internal consistency reliability using Cronbach's coefficient alpha. Convergent validity was assessed in Study 2 using Pearson correlations of the SSGLSS with the OLBI exhaustion and disengagement subscales. Cronbach's alpha was 0.96 in Study 1 and 0.95 in Study 2. Consistent with our hypotheses, there was a small negative correlation between SSGLSS scores and the OLBI exhaustion subscale (r = -0.25, p<0.01) and a moderate negative correlation between SSGLSS scores and the disengagement subscale (r = -0.38, p<0.01). These results suggest that the SSGLSS is a reliable and valid measure of self-efficacy for carrying out support group leadership tasks.